2019
DOI: 10.1021/acs.jpcc.9b02595
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Inhibition Effect of 9-(4-Chlorophenyl)-1,2,3,4-tetrahydroacridines and Tween-80 for Mild Steel Corrosion in Acid Medium

Abstract: The synergistic inhibition effect of Tween-80 and 1,2,3,4-tetrahydroacridines, including 9-(4-chlorophenyl)-2-methyl-1,2,3,4-tetrahydroacridine (CMT) and ethyl 9-(4chlorophenyl)-1,2,3,4-tetrahydroacridine-2-carboxylate (ECT), on mild steel corrosion in 1 M HCl was investigated by using weight loss tests, electrochemical techniques, and surface morphology (SEM/SECM). The results indicated that the mixtures of CMT/ECT and Tween-80 strongly inhibit the corrosion of mild steel compared to individual inhibitors, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Only one constant phase element (CPE), Q st , was included in the circuit to model the corrosion growth at the interface of the electrolyte and the metal. On the other hand, for the case of h -BN-coated ss304, a two-time constant method was employed to obtain the circuits, including Q 1 and Q 2 signifying the CPE magnitude at the coating and the interface, respectively, the resistance of coating ( R 1 ), and the charge-transfer resistance of the metal/coating interface ( R 2 ). …”
Section: Resultsmentioning
confidence: 99%
“…Only one constant phase element (CPE), Q st , was included in the circuit to model the corrosion growth at the interface of the electrolyte and the metal. On the other hand, for the case of h -BN-coated ss304, a two-time constant method was employed to obtain the circuits, including Q 1 and Q 2 signifying the CPE magnitude at the coating and the interface, respectively, the resistance of coating ( R 1 ), and the charge-transfer resistance of the metal/coating interface ( R 2 ). …”
Section: Resultsmentioning
confidence: 99%
“…The synergistic inhibition effect of FYPA and KI can be described by the synergistic parameter S, which is defined using the following formula: S=1I1+21I1+2true′,where I 1+2 = ( I 1 + I 2 ), I 1 is the η of FYPA, I 2 is the η of KI, and I1+2 is the η of FYPA + KI. Generally, S > 1 is indicative of a synergistic effect, whereas S < 1 implies that antagonistic behavior prevails . The S values were calculated on the basis of weight‐loss tests and electrochemical techniques data, and the results are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The thermodynamic study showed that the inhibitors followed the Langmuir adsorption isotherm and underwent physisorption. Zhang et al [ 50 ] designed and synthesized two other tetrahydroacridines ( Figure 3 b), namely 9-(4-chlorophenyl)-2-methyl-1,2,3,4-tetrahydroacridine (CMT) and ethyl 9-(4-chlorophenyl)-1,2,3,4-tetrahydroacridine-2-carboxylate (ECT), which are a slight variation of MPTA and EPTA, respectively, as CIs of mild steel in 1 M HCl. CMT and ECT, at a concentration of 200 ppm, imparted a maximum IE of 98.0% and 93.8%, respectively, via the WL technique.…”
Section: Acridines As Corrosion Inhibitorsmentioning
confidence: 99%